DUKUNGAN ORANG TUA KEPADA REMAJA DI KOTA BOGOR UNTUK MENGONSUMSI SAYUR DAN BUAH[Parental Support for Adolescents’ Vegetable and Fruit Intake in Bogor City] - Asri Christine Lubis; Laras Sekarasih (Universitas Airlangga, 2018)
Compared to children in other cities and towns in the West Java province, adolescents aged 10–14 in Bogor have the lowest rate of vegetable and fruit intake. One primary factor that affects adolescents’ vegetable and fruit intake is parental support. This qualitative descriptive research aimed to analyse parental support for adolescents’ vegetable and fruit intake in Bogor. Fifteen parents whose child studied at a public junior high school in Bogor participated in semi-structured interviews. Findings showed that children’s vegetables and fruits consumption was lower than the Ministry of Health’s recommendation. All parents reported that they provided instrumental support for their children to eat vegetables and fruits at each meal time and provided vegetables and fruits (cooked or bought), but most did not teach or involve their children in preparing vegetables and fruits. Most parents asked their children’s food intake and reminded them to eat more vegetables and fruits as a form of emotional support. However, they did not persuade their children when the latter refused to eat vegetable and fruit. Additionally, parents also did not provide positive feedback for their children when they showed willingness to try to eat vegetables and fruits. Parents seemed to be more lenient in controlling children’s intake of fast food, including purchasing fast foods for their children. The fi ndings suggest a need for an initiative or program that aims at increasing parental support, which necessitates intervention to improve parental support. It is recommended to conduct further research to investigate the predictors of parental support.